EVALUATION OF THE TEXT HEALTH WARNING EFFECTIVENESS ON CIGARETTE’S PACKAGING IN INDONESIA - Sri Widati (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
Smoking prevalence in the low income family is higher than the richest. In Indonesia, amount 63% from 19 million low income families  are a smoker. If they smoke 10 pieces of cigarette everyday, so they spare  Rp 23 billion every year for cigarette expenditure. They still smoke, although there is text health warning on the packaging of cigarette. The text on the cigarrette’s packaging mention that “Cigarettes causing cancer, hypertension, heart attack, impotence, harms baby and pregnancy”. The purpose of this study is to know the effectiveness of text health warning on the cigarette’s packaging. This study is descriptive research using qualitative method. To identify the characteristic of low income family,  smoking behavior, awareness, knowledge, and liking were by structured questionnaire’s interviews. To know what they want about health warning on the cigarette’s packaging was by questionnaires and in dept interview. There were 400 informants. This study did in Surabaya City of Indonesia. The result showed: 1) informant recognized  cigarettes impact from the text health warning on the cigarettes’ packaging. Although they knew the cigarettes’ impact, but they can’t mention the text health warning completely and truly. 2) The text health warning can’t promote the informant’s knowledge about  cigarettes substances and cigarettes impact. 3) Almost all of the informant have no fear feeling while reading the text health warning on the cigarettes’ packaging. It can be concluded that the text health warning on the cigarettes’ packaging do not effectively to promote knowledge and preventive behavior yet. They suggest to use the pictorial health warning to prevent the low income people to not smoking.Keywords: smoking, cigarette, low income family, packaging